Comparative Study of Laparoscopic Appendectomy versus Open Appendectomy at Birat Medical College Teaching Hospital - Yadav, Sanjaya Kumar; Shrestha, Sabin; Koirala, Sanjib; Singh, Ram Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Appendicitis is a commonly encountered surgical problem. Both laparoscopic appendectomy and open appendectomy are common ways of surgical intervention. Objective: The objective of this study was to find the outcome of laparoscopic appendectomy versus open appendectomy in terms of duration of surgery, length of hospital stay, pain, and wound infection at Birat Medical College Teaching Hospital. Methodology: A hospital-based comparative cross-sectional study was conducted from 1 February 2021 to 30 July 2021 among 60 appendicitis patients at the surgery department of Birat Medical College Teaching Hospital. Ethical clearance was taken from the institutional review committee (Ref: IRC-PA-098/2077-78 ) of Birat Medical College Teaching Hospital and informed written consent was taken from each study participant. Collected data were entered in Microsoft Excel and analyzed by SPSS 23. Frequency, mean and standard deviation were used for univariate analysis. Independent sample t-test and chi-square test were used for bivariate analysis and statistical significance was set at 95% confidence interval and p-value less than 0.05. Results: The mean age of the open appendectomy group was 30±16.85 years and the laparoscopic appendectomy group was 33.47 ±13.29 years. The majority were female 32 (53.3%). The mean duration of surgery (p=0.003) and length of hospital stay (p=0.001) was found to be statistically significant between the two groups. Further, no statistically significant difference was found for wound infection (p=0.053). Conclusion: In our centre, despite having more duration of surgery for laparoscopic appendectomy, the length of hospital stay is less. Postoperative pain score at different times and would infection has no difference. Surgeons need to be more informed in both ways of surgeries for its outcome because of no clear-cut better outcomes in either method.